The Role of Vitamin D in Enhancing Immunity and Its Recommendations - Adianto Jaya Nagara; Andry Gonius (PT. Kalbe Farma Tbk., 2021)
Vitamin D is a fat-soluble vitamin with a very important role in regulating the body's calcium balance. It also plays an important role in cell growth, even optimizing the immune system. American Academy of Dermatology recommends supplementation of oral vitamin D to meet daily vitamin D requirements.Vitamin D adalah vitamin larut dalam lemak yang penting untuk mengatur kadar kalsium tubuh, juga berperan dalam pertumbuhan sel dan sistem imun. Untuk memenuhi kebutuhan vitamin D dalam tubuh, American Academy of Dermatology menganjurkan suplementasi oral vitamin D.